PERAN GURU DALAM PENANAMAN KETELADANAN RASULULLAH PADA ANAK USIA DINI DI TKIT ASSHIDDIQ BONE - Irfan, Ahmad; Harianti, Harlisa (EDUCHILD (Journal of Early Childhood Education), 2022)
AbstractThis research discusses the role of teachers in the cultivation of the example of Prophet Muhammad SAW in early childhood at TKIT Asshiddiq Bone which uses qualitative descriptive methods. Data collection is carried out through interviews, observations and documentation, then the data obtained is analyzed by reducing data, presenting data, and drawing conclusions. The results of this study show that teachers play the role of proofreaders, motivators and mentors in instilling the example of the Prophet Muhammad SAW in early childhood at TKIT Asshiddiq Bone, so that children are able to show charitable morals obediently in carrying out worship, polite in speaking, polite in deeds and able to bepatient.